2004
DOI: 10.1111/j.1469-8137.2004.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Legume nodule senescence: roles for redox and hormone signalling in the orchestration of the natural aging process

Abstract: Contents  Summary 1 Introduction 2 The characteristics of legume nodule senescence 3 Redox homeostasis and programmed cell death 6 Antioxidants and programmed cell death during the senescence process  10 Perspectives for manipulating nodule senescence 13 Conclusions and perspectives 14  Acknowledgements 15  References 15 Summary Research on legume nodule development has contributed greatly to our current understanding of plant–microbe interactions. However, the factors that orchestrate root nodule senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
259
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(274 citation statements)
references
References 168 publications
(255 reference statements)
7
259
0
8
Order By: Relevance
“…This induced nodule senescence develops much more rapidly than developmental senescence and present features of oxidative stress and plant cell death (Puppo et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This induced nodule senescence develops much more rapidly than developmental senescence and present features of oxidative stress and plant cell death (Puppo et al, 2005).…”
mentioning
confidence: 99%
“…Developmental nodule senescence has been proposed to result from a decrease in the ascorbategluthatione antioxidant pool coupled to decreasing carbon-to-nitrogen ratios inside the nodule (Puppo et al, 2005). These changes would be sensed and transduced via an abscisic acid-mediated signaling pathway mobilizing proteolytic activities.…”
mentioning
confidence: 99%
“…Since reactive oxygen species (ROS) are involved in the regulation of leguminous nodule senescence [5], the accumulation of ROS was examined in three-week old alfalfa root nodules. DAB staining of H 2 O 2 indicated that much increased levels of H 2 O 2 were generated in the majority of alfalfa root nodules induced by the lsrB1-2 mutant ( Figure 4(b)-(c)), but only slight H 2 O 2 levels were detectable in alfalfa root nodules induced by the wild type strain, S. meliloti 1021 (Figure 4(a)).…”
Section: Oxidative Bursts Emerged In Alfalfa Root Nodules Induced Bymentioning
confidence: 99%
“…In the host plant, ascorbate and glutathione play regulatory roles in delaying nodule senescence, whereas ethylene and abscisic acid promote premature nodule senescence [5]. A large number of host genes are upregulated in aging nodules, as indicated by transcriptomic data.…”
mentioning
confidence: 99%
See 1 more Smart Citation